Penerapan Prinsip GG Dalam Pencegahan Tindak Pidana Korupsi Sektor Pengadaan Barang Dan Jasa - Rizky Rizal; Djuni Thamrin (Jurnal Kajian Ilmiah, 2024)
Procurement of goods and services (PBJ) is a sector that is prone to corruption in Indonesia. Corruption in PBJ can hamper national development, harm state finances, and reduce public trust in the government. It is hoped that the implementation of GG in PBJ can prevent criminal acts of corruption. The aim of this research is to explore and analyse the application of GG principles in efforts to prevent criminal acts of corruption in the goods and services procurement sector. This research uses a qualitative approach. Data collection techniques in this research were carried out using desk studies and literature reviews. The research results show that in the goods and services procurement sector, the application of GG principles is needed to reduce corruption and increase transparency and accountability in budget management and accounting. Procurement of goods and services in local governments must refer to the principles of GG, by implementing transparency, accountability, efficiency, effectiveness, and responsibility. Efforts to reduce corruption and increase the balance of income and expenditure. The application of GG principles in the goods and services procurement sector can reduce corruption and increase the balance of income and expenditure in local governments.